Inhibiting HMGB1 with Glycyrrhizic Acid Protects Brain Injury after DAI via Its Anti-Inflammatory Effect - Honggang Pang; Tinqin Huang; Jinning Song; Dandong Li; Yonglin Zhao; Xudong Ma (Mediators of Inflammation)
High-mobility group box 1 (HMGB1), a nuclear protein that has endogenous cytokine-like activity, is involved in several neurological diseases by mediating inflammatory response. In this study, a lateral head rotation device was used to establish a rat diffuse axonal injury (DAI) model. The dynamic expression of HMGB1, apoptosis-associated proteins, and proinflammatory cytokines were detected by Western blot, and neuronal apoptosis was observed by TUNEL staining. The extracellular release of HMGB1 and the accumulation of β-APP were observed by immunofluorescence and immunohistochemistry, respectively. The brain injury was indicated by modified neurological severity score (mNSS), brain water content (BWC), and the extravasation of Evans blue. We showed that HMGB1 level obviously decreased within 48 h after DAI, accompanied by neuronal apoptosis, the activation of caspases 3 and 9, and the phosphorylation of BCL-2. Inhibiting HMGB1 with glycyrrhizic acid (GL) can suppress the activation of apoptosis-associated proteins and inhibit the expression of proinflammatory cytokines, which ameliorated motor and cognitive deficits, reduced neuronal apoptosis, and protected the integrity of blood brain barrier (BBB) and axonal injury after experimental DAI in rats. Thus, HMGB1 may be involved in the inflammatory response after DAI, and inhibition of HMGB1 release with GL can notably alleviate the brain injury after DAI.